US hegemony and regime change in Latin America. Issue 2 (17th February 2019) - Schenoni, Luis L.; Mainwaring, Scott
ABSTRACT: We contribute to the extensive literature on international influences on democratization and democratic breakdowns by conceptualizing hegemonic mechanisms of regime change and assessing them empirically. Our findings are based on a multi-methods approach and highlight the varying importance of hegemonic influences in post-1945 Latin America. We argue that US support for democratization was consistent in the wave of transitions to democracy that began in Latin America in 1978 and that it was decisive in many of these transitions. While past work has attributed responsibility to the US for the waves of democratic breakdowns from 1948 to 1956 and 1964 to 1976, an examination of the 27 breakdowns from 1945 to 2010 gives reason to doubt this interpretation. Future research could use these conceptual and methodological tools to explore the role of other powers in waves of democracy and authoritarianism.